Kajian Ekokritik terhadap Sepilihan Puisi Ibrahim Gibra - Rudi S. Tawari; Fachmi Alhadar (Humanitatis : Journal of Language and Literature, 2022)
This paper aims to study the poetry of Ibrahim Gibra. Through the medium of poetry, Ibrahim Gibra conveyed his anxiety about the environment. The data in this study were sourced from the book Karang Menghimpun Bayi Kerapu (2019). The method used is descriptive qualitative. While the approach used is ecocriticism. Through this method and approach, this research succeeded in describing poetry as a medium for Gibra to express his anxiety about environmental damage. Gibra's childhood and career opportunities in the capital city of Jakarta even seem to give legitimacy to his anxiety. Childhood experiences and work that gave him enough space to travel to various cities in Indonesia gave the poet an opportunity to portray the reality. As a portraitist, Gibra has chosen a broad perspective to capture not only beauty, but also the inherent value as a result of the creation of beauty or the threat that is ready to rob it and replace it with disaster. For example, Jakarta is a magnet for many people and is considered the pinnacle of progress in the civilization of the Indonesian nation, seen by the poet with one eye. As someone who was born and grew up in a humble village, the poet, in his poems, has a longing to return home. The dictions used in his poems, especially the word “dew” which appears most often, seem to represent the longing for freshness, purity, and simplicity.